2006
DOI: 10.1111/j.1471-4159.2005.03578.x
|View full text |Cite
|
Sign up to set email alerts
|

Presenilin clinical mutations can affect γ‐secretase activity by different mechanisms

Abstract: Mutations in human presenilin (PS) genes cause aggressive forms of familial Alzheimer's disease. Presenilins are polytopic proteins that harbour the catalytic site of the c-secretase complex and cleave many type I transmembrane proteins including b-amyloid precursor protein (APP), Notch and syndecan 3. Contradictory results have been published concerning whether PS mutations cause 'abnormal' gain or (partial) loss of function of c-secretase. To avoid the possibility that wild-type PS confounds the interpretati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

42
353
2
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 386 publications
(406 citation statements)
references
References 48 publications
(108 reference statements)
42
353
2
7
Order By: Relevance
“…1B ), thereby validating our substrate and cell-based system. Interestingly, and in contradiction with observations reported by Bentahir et al [10], the same PS1- and PS2-expressing cells that generated different amounts of Aβ generated equal amounts of AICD-GVP as measured by both a neo-epitope ELISA specific for the N-terminus of AICD (Fig. 1C ) and a Luciferase reporter gene assay (Fig.…”
Section: Resultscontrasting
confidence: 95%
See 4 more Smart Citations
“…1B ), thereby validating our substrate and cell-based system. Interestingly, and in contradiction with observations reported by Bentahir et al [10], the same PS1- and PS2-expressing cells that generated different amounts of Aβ generated equal amounts of AICD-GVP as measured by both a neo-epitope ELISA specific for the N-terminus of AICD (Fig. 1C ) and a Luciferase reporter gene assay (Fig.…”
Section: Resultscontrasting
confidence: 95%
“…Conditioned media was then harvested for Aβ ELISA at the same time that cell lysates were harvested for AICD-GVP ELISA or Luciferase assay. Consistent with previous reports [10, 11, 13], the Aβ ELISA demonstrated that PS1 generates approximately five-fold more Aβ than PS2 (Fig. 1B ), thereby validating our substrate and cell-based system.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations